(untitled) (Global Journal of Management and Business Research, 2020)
The aim of the study was to evaluate the effect of forwards contracts on the financial performance of multinational companies in Kenya. The study used descriptive and crosssectional research designs. The population consisted of nine companies listed at Nairobi securities exchange under the banking sector and one form the energy sector. The sample size of this study was three companies. Purposive sampling was applied to arrive at the sample size of three Multinational companies. Secondary data was collected from published annual financial reports for ten years from 2009-2018. Descriptive and inferential methods were applied to analyze the obtained data. The findings of the analysis were presented using tables and figures. The study found out that forward contracts had a positive correlation with the financial performance of multinational companies. The study concluded that forwards had direct and statistically insignificant effects on financial performance.